EFEKTIVITAS METODE TUTOR SEBAYA DALAM PENCAPAIAN KOMPETENSI ASUHAN PERSALINAN NORMAL PADA PEMBELAJARAN LABORATORIUM DI PRODI DIII KEBIDANAN UNUSA - Dwi Anggraini, Fritria; Puji Rahayu, Esty (Unusa Press, 2016)
Peer tutoring method is one method of learning which the coaching or the instruction was given by the students that designated as a tutor or have the highest capability to another students who have the moderate and low ability, and they are friends of the class. Tutors are selected from the results of the pretest and then guiding their friends until they get competent in doing Normal Delivery Care to the phantom. This study is aiming to determine the differences of the effectiveness of peer tutoring methods towards the attainment competency of Normal Delivery Care in the lab subject between classes 2A and 2B in Prodi DIII Midwifery UNUSA. The research design was pretest-posttest design. The population in this research were all fourth semester’s students of the DIII Midwifery UNUSA that is 93 people. The sample of this research are 21 people from class 2A and 27 people from class 2B with proportional random sampling technique. Data collection technique were observation. Analysis of data using statistical test two samples t-test. Presentation of data with figures and tables. The entire value of the respondents increased as compared to the value at the time posttest pretest.  The average difference between pretest and posttest in class 2A is 19.87 and in class 2B is 16.73. Then performed statistical tests are two-sample t-test with significance = 0.05; obtained t = 2.006 and ttable = 1.706. Therefore thitung (2.006)> ttable (1.706), then Ho is rejected, it means that there are differences in the effectiveness of peer tutoring methods towards the attainment of Normal Delivery Care in the learning lab between classes 2A and 2B in Prodi DIII Midwifery UNUSA.